2018
DOI: 10.1186/s12886-018-0943-7
|View full text |Cite
|
Sign up to set email alerts
|

Universal ocular screening of 481 infants using wide-field digital imaging system

Abstract: BackgroundUniversal ocular screening of infants is not a standard procedure in children’s health care system in China. This pilot study investigated prevalence of ocular abnormalities of 6 weeks-age infants using wide-field digital imaging system.MethodsInfants aged 6 weeks around were consecutively enrolled in a public hospital between April 2015 and August 2016. All the infants who were enrolled in the study underwent vision assessment, eye position examination, external eye check, pupillary light reflex, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 17 publications
2
31
2
4
Order By: Relevance
“…A few large studies in India and China found that abnormal ocular findings in this group of newborns ranged from 4 to 25% (3)(4)(5). A pilot study screening 481 older infants at six weeks of age in China found up to 41.2% abnormal ocular findings (6). Abnormal ocular findings detected included subconjunctival haemorrhage, congenital microphthalmos, congenital corneal leukoma, posterior synechia, persistent pupillary membrane, congenital cataract, retinoblastoma, optic nerve defects, vitreous haemorrhage, congenital glaucoma, uveal coloboma and so on (3,4).…”
Section: Introductionmentioning
confidence: 81%
“…A few large studies in India and China found that abnormal ocular findings in this group of newborns ranged from 4 to 25% (3)(4)(5). A pilot study screening 481 older infants at six weeks of age in China found up to 41.2% abnormal ocular findings (6). Abnormal ocular findings detected included subconjunctival haemorrhage, congenital microphthalmos, congenital corneal leukoma, posterior synechia, persistent pupillary membrane, congenital cataract, retinoblastoma, optic nerve defects, vitreous haemorrhage, congenital glaucoma, uveal coloboma and so on (3,4).…”
Section: Introductionmentioning
confidence: 81%
“…Estamos de acuerdo con el criterio de realizar el control oftalmológico lo antes posible ya que encontramos que hubo una relación estadísticamente significativa entre menores de 28 días de vida y anormalidades oculares. En la metodología de examinación, coincidimos con otros autores en el uso de colirio de proparacaína, blefaróstato e indentador escleral cuando fue necesario para la realización del examen 10 , no se registraron complicaciones oculares posteriores al mismo 12 . En nuestra institución el sistema de toma de imágenes se realizó con un Smartphone para documentar los hallazgos, consideramos que es una herramienta útil para evaluar la evolución de las lesiones.…”
Section: Discussionunclassified
“…En nuestra institución el sistema de toma de imágenes se realizó con un Smartphone para documentar los hallazgos, consideramos que es una herramienta útil para evaluar la evolución de las lesiones. Los hallazgos patológicos oculares tuvieron relación significativa con los antecedentes patológicos de la madre y del niño 12 . El antecedente de patologías TORCH fue frecuente como antecedente materno y como consecuencia también en los bebés examinados, representado un problema importante en los países subdesarrollados.…”
Section: Discussionunclassified
See 2 more Smart Citations